Agricultural Development through Regional Approach: A Case Study in Poultry Production Central Area in Mungka Sub-district, Lima Puluh Kota District - Sri Endang Kornita, Sjafrizal, Helmi, Asdi Agustar (Universitas Andalas, 2018)
The regional approach in agricultural development has only been limited to the concept and has not been implemented in real terms. Various forms and models of agricultural development policy using the regional approach cannot prove that the indicators of regional approach have existed and been applied in agricultural areas. The development of agriculture so far has only been sectoral. This indicates that the concept of agricultural development through regional approach has not been implemented in real condition. In development through regional approach, the synergies among sectors and among economic activities are compulsory. The production central area (PCA) approach is one of the agricultural development approaches based on regional economic development theory. This research aimed to assess how area production center as a model of agricultural development that had considered regional concept, could be success in developing regions. The respondents were layer hen breeders residing in PCA location and Non PCA (50 respondents each).The study reveals that the value of agglomeration profits of large scale economies (SEI), localization economies (LEI), capital and labor showed positive and significant effects on layer hen production at PCA location. To further increase commodity production in PCA, the agglomeration profits as a regional approach variables should be part of the PCA analysis to improve productivity, efficiency and provide added value for farmers/breeders.